المعتقدات الصحية وعلاقتها بفاعلية الذات لدى طلبة الجامعة (Journal Of Educational and Psychological Researches, 2013)
Off by the idea of ​​health beliefs to promote health and conservation. It occupies beliefs health and health behavior and development of growing importance, not in terms of physical health, but also in terms of mental health also so highlights the importance of beliefs health through raising awareness of social health and contribute to the Carissa most dangerous enemy facing human not a disease, as well as focus on the role of the individual in personal responsibility for his health because this will result to be aware of the risk factors and address them early and disease prevention and physical ills and improve mental state and then to maintain overall health.According to Bandura Bandura that the effectiveness of self-determined choice of activities or events that face us as according to the theory of expectations of self-efficacy for Pandora (Bandora, 1977, 1986), the individual in order that the health behavior, the intention is not generated only when possesses in addition to expectations possible outcome (outcomeexpectance) efficiency matching expectations or appropriate at the same time. That is, the person not only believe that smoking is harmful to health, for example, in order to stop smoking, but he has to be convinced that it is able to withstand the difficult process of quitting smoking. Targeting Current searchdo you know the level of health beliefs among university students.1 2- Know the level of effectiveness of self among the students of the university. 3- know the difference in the health belief according to the variables of sex (male / female) and specialization (scientific / humanist)-4-  Know the correlation between health belief and self-effectiveness of university students.The researcher building measure of beliefs health according to the theory adopted and extracted characteristics Alsekoumtria while has adopted a measure (Alalusi, 2001) of the effectiveness of the self and the Pttbaiqama the research sample, amounting to (200) students of the university students were selected randomly and after using statistical methods appropriate researcher reached to several conclusions, including1-The current sample have health belief1self-- that the current sample have effective 2 3- appeared there a statistically significant difference in the health beliefs according to sex variable in favor of female ,4- There are no statistically significant difference in the health beliefs according to specialization variablesand a positive relationship between health beliefs and self-effectiveness of university students In light of the results of this research came researcher with many of the recommendations and proposals